Total Synthesis of (+)-Eburnamonine - Prasad, Kavirayani R.; Nidhiry, John E. (Synlett, 2012)
The enantiospecific total synthesis of vinca alkaloid (+)-eburnamonine is accomplished from l-ethyl lactate. Key feature of the synthesis is the construction of the chiral quaternary center involving a Johnson–Claisen rearrangement and assembly of the pentacyclic core by the Pictet–Spengler reaction and ring-closing metathesis.
Keywords: eburnamonine; alkaloids; l-ethyl lactate